THE INFLUENCE OF WORKPLACE SPIRITUALITY, ISLAMIC WORK ETHICS, ON EMPLOYEE ORGANIZATIONAL COMMITMENT IN ISLAMIC BANKING IN MEDAN CITY - Muhammad Andi Prayogi; Asmuni Asmuni; Yenni Samri Juliati Nasution (Proceeding International Seminar of Islamic Studies, 2021)
This study aims to see the influence of Workplace Spirituality, Islamic Work Ethics on Organizational Commitment. This type of research is quantitative that uses primary data by distributing questionnaires to 138 respondents who were employees of Islamic Banking in Medan City. Data analysis techniques used SPSS 24 with multiple linear regression. The results of the study partially and simultaneously Workplace Spirituality, Islamic Work Ethic affects Organizational Commitment.  Keywords: Workplace Spirituality, Islamic Work Ethics, Organizational Commitment